Islandų pasakos ir sakmės / Icelandic fairy-tales and legends - Vijūnas, Aurelijus (Scandinavistica Vilnensis, 2015)
This collection of Icelandic folklore contains over 100 texts, including fairy tales, legends, folk beliefs, as well as excerpts from medieval Icelandic sagas. Most of the texts presented in this volume have been translated into Lithuanian for the first time.Į šį rinkinį įtraukta virš šimto islandų liaudies pasakų, sakmių, prietarų bei ištraukų iš viduramžių islandų sagų. Dauguma šioje knygoje pristatomų tekstų į lietuvių kalbą išversti pirmą kartą.
Keywords: Icelandic folklore; translation into Lithuanian